ANALISIS DEIKSIS PADA PERCAKAPAN MAHASISWA SEMESTER VI PRODI PENDIDIKAN BAHASA DAN SASTRA INDONESIA FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS NIAS RAYA TAHUN 2022 - Laia, Wajarman (Universitas Nias Raya, 2023)
This research was motivated by the researcher's concern and curiosity about deixis in the conversations of sixth semester students of the Indonesian Language and Literature Education Study Program, Faculty of Teacher Training and Education, Nias Raya University 2022. Apart from that, the researcher also wanted to deepen knowledge about deixis. Therefore, the researcher found deixis in the conversation of students in the sixth semester of the Indonesian Language and Literature Education Study Program, Faculty of Teacher Training and Education, Nias Raya University 2022. This deixis includes person deixis, pointing deixis, place deixis, time deixis and discourse deixis. There are ten personal deixis, three demonstrative deixis, seven place deixis, three time deixis and one discourse deixis. Furthermore, the researcher suggests that other prospective researchers who will conduct further research regarding deixis in Indonesian students' conversations, or similar deixis with relevant objects, are advised to conduct deeper, more thorough and more detailed research regarding the forms of deixis found in conversations. Indonesian language students, namely, person deixis, demonstrative deixis, place deixis, time deixis and discourse deixis. Therefore, researchers still have limitations, so it is hoped that future researchers can perfect this research.